2020
DOI: 10.21203/rs.3.rs-30029/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graphene-Modified CePO4 Nanorods Effectively Treat Breast Cancer-Induced Bone Metastases and Regulate Macrophage Polarization to Improve Osteo-Inductive Ability

Abstract: Background Breast cancer bone metastasis has become one of the most common complications; however, it may cause cancer recurrence and bone nonunion and local bone defects.Methods Herein, In vitro, we verified the effect of bioscaffold materials on cell proliferation and apoptosis through CCK8 experiment, staining of living dead cells, and flow cytometry. We used immunofluorescence technology and flow cytometry to verified whether bioscaffold materials regulated the polarization of macrophages, and we use ALP s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…59 Molecular analysis has shown that Ca 2+ , Zn 2+ , La 3+ , and Cerium ions (Ce 3+ ) play these roles by regulating the TGF-β/Smad signaling pathway, which is the key pathway to osteoblast development. 60,61 TGF-β can bind to its type II receptors and then activate type I receptors. Activated type I receptors lead to the phosphorylation of Smad 2 or Smad 3, which can form a complex with Smad 4 and enter the nucleus.…”
Section: Function Of Metal Ions In the Treatment Of Bone Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Molecular analysis has shown that Ca 2+ , Zn 2+ , La 3+ , and Cerium ions (Ce 3+ ) play these roles by regulating the TGF-β/Smad signaling pathway, which is the key pathway to osteoblast development. 60,61 TGF-β can bind to its type II receptors and then activate type I receptors. Activated type I receptors lead to the phosphorylation of Smad 2 or Smad 3, which can form a complex with Smad 4 and enter the nucleus.…”
Section: Function Of Metal Ions In the Treatment Of Bone Defectsmentioning
confidence: 99%
“…However, the specific mechanism of La 3+ promoting angiogenesis has not been thoroughly studied, and the mechanism is not clear. 40,61…”
Section: Function Of Metal Ions In the Treatment Of Bone Defectsmentioning
confidence: 99%
“…GO can serve as an immunostimulant to activate the host's immune system because they can reduce ROS production in cells, thus changing the repolarization of macrophages and regulating the immune response of the body [78,84]. It has been demonstrated that the earlier shift of macrophage phenotypes to the M2 type and ROS regulation in inflammation-stimulated macrophages play significant roles in M1 macrophage treatment [85,86]. Therefore, Wang et al [87] formulated a hybrid nanocomposite by coating magnetite nanoparticles with reduced graphene oxide (rGO) and followed by PEG-NH 2 modification on their surface.…”
Section: Graphene-based Nanomaterialsmentioning
confidence: 99%
“…They all belong to Ce 3+ , which means that the as-synthesized F-CePO 4 mainly contains positive trivalent Ce elements. 26,27 The morphology of F-CePO 4 was observed by SEM. As shown in Fig.…”
Section: Structure and Morphology Characterizationmentioning
confidence: 99%